The passage of time to develop ethical business environment through Malaysia’s Competition Act 2010 and competition agenda : post World War II to present days - Sasikala, Sankaran; Hasnah, Haron; Teoh, Ai Ping; Yuvaraj, Ganesan (KnE Social Sciences, 2019)
This article seeks to reflect on the background of Competition Act 2010 of Malaysia by taking a step by step view on the many initiatives undertaken by various world bodies from post-World War II era in reviving and rebuilding the world economy to present days involving the competition agenda of the nation. In doing so, this article intends to emphasize on the perseverance and continuous efforts made over the decades in ensuring the nation finally had established the Act and the unceasing continuous efforts in forming ethical business environment with healthy competition stay as part Government of Malaysia’s initiatives.